Effect OF Film Thickness And Annealing Time on Structural And Optical Propertieis Of The Oxides (Fe2030, Co304) And Their Mixtures - Maki, S. A. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
Thin film technology is one of the most important technologies that have contributed to the development of semiconductors and their applications in several industrial fields. The Iron Oxides (Fe20) and (Co3O4) thin films and their applications are of importance, in that these two materials are considered as important industrial materials, and used in spectrally selective coating, temperature sensors, resistive heaters, and photo cells. Thin films of Iron Oxide (Fe20,), Cobalt Oxide (Co304) and their mixtures in different ratios (75:25, 50:50, 25:75) were prepared by the method of chemical spray pyrolysis deposition at different thicknesses (77s t S200) nm on cover-glass substrates: thickness of (1) mm at temperature (653)OK, and at temperature (753)oK for (one, and two) hour. The nature of the thin-films surfaces are examined by optical microscopy, while the crystallinity of the compounds is examined by X ray diffraction (XRD) The results of KRD) have shown that the films of (Fe20,) and (Co304) and their mixtures are of amorphous structure. Annealing operations led to transition of the films’ structure from the amorphous to polycrystalline state. These obtained results were found in agreement with the American Standard for Testing Materials (ASTM). Film thickness, and annealing time were investigated, the results show the crystallite size increases with the increase of the thickness of the thin film The increase in the annealing time for more than one hour resulted in the appearance of some peaks in diffraction spectrum of the prepared films. This verifies that it is polycrystalline, and this increases the time to organize itself in the crystalline lattice and decreases the crystalline defect. This research also included the study of the optical properties of the prepared samples by recording the absorption and transmission spectrum over the spectral range (200-900 nm, the optical energy gap for the allowed direct transition was evaluated. In general, the optical energy gap decreases with increase of the film thickness percentage of (Co3O4) in the sample, and it increases after annealing The optical parameters are investigated and calculated such a optical absorption coefficient, photon energy, and the width of localized states too. It is found that the values of absorption coefficient the increases with increasing percentage of (Co3O4)